EFEKTIVITAS PENGGUNAAN MEDIA AUGMENTED REALITY UNTUK MENINGKATKAN PEMAHAMAN KONSEP GEOMETRI PADA SISWA SMP - Mei, Maria Fatima; Seto, Stefania Baptis; Meke, Konstantinus Denny Pareira; Woe, Emerensiana; Didin, Mohamad (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
Static and three-dimensional models often used in textbooks or blackboards are usually insufficient to help students understand the concepts of three-dimensional space in depth. The purpose is to find out students' learning activities using Geogebra media based on Augmented Reality (AR) on spatial geometry material, (2) To find out the increase in student's conceptual understanding through the use of Geogebra media based on Augmented Reality (AR) on spatial geometry material. This type of research is called Classroom Action Research (CAR). The subjects in this study were students of class VII of SMP Negeri 2. This research was conducted in class VII of SMP N 2 Ende. Data collection techniques in this study were observation, tests, and documentation. The instruments used in this study were observation sheets conceptual understanding tests and documentation. The data analysis technique used was observation guidelines, and conceptual understanding of test data, for the criteria for implementing teacher and student activity guidelines. The results of the study showed: an increase in the ability to understand geometric concepts by 42% after the cycle II learning process was carried out. While student activity increased by 42%. Therefore, it can be concluded that the use of Augmented Reality media based on geometry can improve the conceptual understanding of class VII students of SMP Ende Negeri 2.